Additions to Phaeoramularia species - SANJAY K. SINGH* and P.N. SINGH, RITESH K. CHAUDHARY (Indian Phytopathology, 2002)
This paper includes 3 new species of hyphomycetous genus Phaeoramularia Munt. Viz., P. dicanthii-annulatae, P.erigeronis and P. rosigena collected on living leaves of Dicanthium annulatum, Erigeron asteroides and Spiraea bella respectively. They are compared with allied taxa, particularly those occurring on same host genus or on the host family.